if x+y+z=12and x2+y2+z2=62 then find xy+yz+zx.
Answers
Answered by
14
Here's your answer !!
__________________________
![= x + y + z = 12 = x + y + z = 12](https://tex.z-dn.net/?f=+%3D+x+%2B+y+%2B+z+%3D+12)
By squaring both side ,we get :-
![{(x + y + z)}^{2} = {(12)}^{2} {(x + y + z)}^{2} = {(12)}^{2}](https://tex.z-dn.net/?f=+%7B%28x+%2B+y+%2B+z%29%7D%5E%7B2%7D+%3D+%7B%2812%29%7D%5E%7B2%7D+)
![{x}^{2} + {y}^{2}+{z}^{2} + 2xy + 2yz + 2zx = 144 {x}^{2} + {y}^{2}+{z}^{2} + 2xy + 2yz + 2zx = 144](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D+%2B+%7By%7D%5E%7B2%7D%2B%7Bz%7D%5E%7B2%7D+%2B+2xy+%2B+2yz+%2B+2zx+%3D+144)
![( {x}^{2} + {y}^{2} + {z}^{2} ) + 2(xy + yz + zx )= 144 ( {x}^{2} + {y}^{2} + {z}^{2} ) + 2(xy + yz + zx )= 144](https://tex.z-dn.net/?f=+%28+%7Bx%7D%5E%7B2%7D+%2B+%7By%7D%5E%7B2%7D+%2B+%7Bz%7D%5E%7B2%7D+%29+%2B+2%28xy+%2B+yz+%2B+zx+%29%3D+144+)
![given= {x}^{2} + {y}^{2} + {z}^{2} = 62 given= {x}^{2} + {y}^{2} + {z}^{2} = 62](https://tex.z-dn.net/?f=+given%3D+%7Bx%7D%5E%7B2%7D+%2B+%7By%7D%5E%7B2%7D+%2B+%7Bz%7D%5E%7B2%7D+%3D+62)
![= 62 + 2(xy + yz + zx) = 144 = 62 + 2(xy + yz + zx) = 144](https://tex.z-dn.net/?f=%3D+62+%2B+2%28xy+%2B+yz+%2B+zx%29+%3D+144)
![= 2(xy + yz + zx) = 144 - 62 = 2(xy + yz + zx) = 144 - 62](https://tex.z-dn.net/?f=+%3D+2%28xy+%2B+yz+%2B+zx%29+%3D+144+-+62)
![= 2(xy + yz + zx) = 82 = 2(xy + yz + zx) = 82](https://tex.z-dn.net/?f=+%3D+2%28xy+%2B+yz+%2B+zx%29+%3D+82)
![= xy + yz + zx = \frac{82}{2} = xy + yz + zx = \frac{82}{2}](https://tex.z-dn.net/?f=+%3D+xy+%2B+yz+%2B+zx+%3D+%5Cfrac%7B82%7D%7B2%7D+)
![= > xy + yz + zx = 41 = > xy + yz + zx = 41](https://tex.z-dn.net/?f=+%3D+%26gt%3B+xy+%2B+yz+%2B+zx+%3D+41)
Hence,
![= > xy + yz + zx = 41 = > xy + yz + zx = 41](https://tex.z-dn.net/?f=+%3D+%26gt%3B+xy+%2B+yz+%2B+zx+%3D+41)
___________________________
Hope it helps you! :)
__________________________
By squaring both side ,we get :-
Hence,
___________________________
Hope it helps you! :)
Answered by
11
Given:- x+y+z=12 and x²+y²+z²=62
then to find:- xy+yz+zx,
x+y+z=12
Squaring both sides,
(x+y+z)² = (12)²
⇒x²+y²+z²+2xy+2yz+2zx = 144
⇒ 62 + 2(xy+yz+zx) = 144
⇒ 2(xy+yz+zx) = 144-62
⇒ xy+yz+zx = 82/2
⇒ xy+yz+zx = 41
BE BRAINLY. LOVE BRAINLY
Similar questions